Psychological Readiness of Young People for Early Marriage - Hrytsiuk, Iryna; Mahdysiuk, Liudmyla; Tryhub, Halyna; Khnykina, Oksana; Mariia, Zameliuk (My University, 2022)
The institution of the family in the conditions of dynamic development of society has undergone significant changes in Ukraine. Young people are actively realizing themselves in various spheres of public life. But emotions and feelings remain a relevant factor that influences the choice of the future path, in particular the feeling of love, which is relevant for any age, but still in young people, more emotionally colored. At the moment, there is a disappointing picture in Ukraine, the number of divorces and single-parent families is growing, the nation is aging, the birth rate is declining, the living standards are deteriorating, and the value of the family is as such is declining. All of the above usually affects the readiness to start a family, contributes to the postponement of marriage, and weakens the motivation to procreate. In this article, we offer a study that empirically demonstrates the level of readiness of young people for early marriage. The research was conducted on the basis of Lesya Ukrainka Volyn National University. We obtained up-to-date results that demonstrated a high subjective level of readiness of young people for early marriage. Factors that demonstrate the objective level of unpreparedness of young people for marital relationships were also identified. Because young people at an early age show a fairly low level of personal maturity, responsibility, and independence. Thus, we can conclude that young people want a healthy partnership, but in a symbiotic relationship, they quite rarely pay attention to objective factors such as personality traits, character, actions, both their own and partner. Being on the stage of a romantic relationship, they feel emotional uplift, idealize a partner, and their expectations regarding family life. But according to empirical data, at a young age you should work on the development of your own identity, the ability to interact effectively with others, resolve conflicts, hear yourself and your desires, strive for self-realization. But in the future, having reached a certain level of maturity, to fully realize the potential of their capabilities, create a well-functioning family that will develop, change, transforms, for the benefit of all its members.
Keywords: Love; Marriage; Readiness for Marriage; Family; Youth; Maturity